2006
DOI: 10.1242/jcs.03015
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct pools of Src family tyrosine kinases regulate PDGF-induced DNA synthesis and actin dorsal ruffles

Abstract: The mechanism by which the Src family of protein-tyrosine kinases (SFKs) regulate mitogenesis and morphological changes induced by platelet-derived growth factor (PDGF) is not well known. The cholesterol-enriched membrane microdomains, caveolae, regulate PDGF receptor signalling in fibroblasts and we examined their role in SFK functions. Here we show that caveolae disruption by membrane cholesterol depletion or expression of the dominant-negative caveolin-3 DGV mutant impaired Src mitogenic signalling includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 64 publications
8
57
0
Order By: Relevance
“…These data show that all agents activated Src. Although the magnitude of the increase in phosphorylation was modest, it is consistent with what other groups report using this approach (30,64) and what we have found using a different approach to monitor activation of SFKs (43). B, mouse embryo fibroblasts that lacked all SFKs (39) were reconstituted with either an empty expression vector (Ϫ/Ϫ), or wild type c-Src (Src) (40) and stimulated with the indicated agents as described in panel A.…”
Section: Indirect Activation Of Pdgfr␣ Promoted Proliferation and Sursupporting
confidence: 91%
“…These data show that all agents activated Src. Although the magnitude of the increase in phosphorylation was modest, it is consistent with what other groups report using this approach (30,64) and what we have found using a different approach to monitor activation of SFKs (43). B, mouse embryo fibroblasts that lacked all SFKs (39) were reconstituted with either an empty expression vector (Ϫ/Ϫ), or wild type c-Src (Src) (40) and stimulated with the indicated agents as described in panel A.…”
Section: Indirect Activation Of Pdgfr␣ Promoted Proliferation and Sursupporting
confidence: 91%
“…Ras and Rab5 pathways have also been documented (Lanzetti et al, 2004), and we have recently shown that this response implicates Src family tyrosine kinases (SFK). In addition, our results suggest that in contrast to Src mitogenic function, SFK signal transduction promoting actin assembly does not require receptor association (Veracini et al, 2006). Rather, it involves the lipid second messenger sphingosine-1-phosphate, which may activate SFK through a seven-transmembrane receptor of the EDG family and an associated heterotrimeric Gi protein.…”
mentioning
confidence: 74%
“…This potentiating effect was specific to dorsal ruffles as lateral ruffles were not (Manes et al, 2000) were subcloned into pBABE. Cell culture, transfection, infection, immunofluorescence analysis, Q-PCR and biochemistry have been described by Veracini et al (2006). White arrows indicate cells with dorsal ruffles.…”
Section: Slap Negatively Regulates Pdgf-induced Dorsal Rufflesmentioning
confidence: 99%
“…Moreover, Csk relocalization to these membranes induced, at most, a 50% reduction of SFK activity, confirming that it does not target all pools of SFK present in these cells. Accordingly, spatial regulation has been considered as an important feature of signal specificity induced by SFK in nontransformed cells (Veracini et al, 2006(Veracini et al, , 2008, and this may apply for transformed cells as well. For example, when localized at focal adhesions, SFK has important roles in cell growth and survival (Frame, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Purified FynK298M (FynK À ) was described in Koegl et al (1994). Anti-SFK (cst1) was described in Veracini et al (2006); anti-Src specific (2.17) antibody was a generous gift from Dr S Parsons (University of Virginia, VA, USA). Anti-Csk was described in Be´nistant et al (2001), anti-PAG in Veracini et al (2008) and anti-Cbp in Oneyama et al (2008).…”
Section: Methodsmentioning
confidence: 99%